Predicting Water Quality Parameters in a Complex River System - Kurniawan I.; Hayder G.; Mustafa H.M. (Polish Society of Ecological Engineering (PTIE), 2023)
This research applied a machine learning technique for predicting the water quality parameters of Kelantan River?using the historical data collected from various stations. Support Vector Machine (SVM) was used to develop the?prediction model. Six water quality parameters (dissolved oxygen (DO), biochemical oxygen demand (BOD),?chemical oxygen demand (COD), ammonia nitrogen (NH3-N), and suspended solids (SS)) were predicted. The?dataset was obtained from the measurement of 14 stations of Kelantan River from September 2005 to December?2017 with a total sample of 148 monthly data. We defined 3 schemes of prediction to investigate the contribution?of the attribute number and the model performance. The outcome of the study demonstrated that the prediction?of the suspended solid parameter gave the best performance, which was indicated by the highest values of the?R2 score. Meanwhile, the prediction of the COD parameter gave the lowest score of R2 score, indicating the difficulty?of the dataset to be modelled by SVM. The analysis of the contribution of attribute number shows that the?prediction of the four parameters (DO, BOD, NH3-N, and SS) is directly proportional to the performance of the?model. Similarly, the best prediction of the pH parameter is obtained from the utilization of the least number of?attributes found in scheme 1. 2020. The American Society of Hematology. All Rights Reserved.